Polymer processing principles and modeling - Agassant, J.-F (Hanser Publishers, 2017)
Engineering of polymers is not an easy exercise: with evolving technology, it often involves complex concepts and processes. This book is intended to provide the theoretical essentials: understanding of processes, a basis for the use of design software, and much more.